Sex-divergent anatomic system concordance in second primary malignant neoplasms: a large-scale analysis - Liu, Yadong; Shi, Linping; Han, Wei; Duan, Xuejuan; Lv, Pintian; Li, Na; Zhang, Xianbo; Liu, Jinlong; Zhao, Jing (Frontiers in Oncology, 2026)
ObjectiveUsing a second primary cancers (SPCs) database, this study aimed to analyze the epidemiological characteristics, systemic distribution, and correlation patterns of primary and SPCs across sexes. The goal was to identify potential sex-specific patterns and provide a reference for clinical prevention, diagnosis, and treatment.MethodsClinical data of 918 patients with SPCs from two centers were retrospectively analyzed. Basic characteristics were summarized by sex. The systemic and specific type distributions of both primary and SPCs were analyzed. Association analyses explored cancer combination patterns and the tendency for subsequent cancers within the same system.ResultsThe cohort included 455 males (49.6%) and 463 females (50.4%), showing a balanced sex distribution (χ² = 0.143, P = 0.705). Primary cancers were predominantly located in the respiratory (298 cases), digestive (252 cases), and reproductive (161 cases) systems. SPCs were also most frequent in the respiratory (369 cases) and digestive (266 cases) systems. Stratified by sex, females exhibited higher proportions of cancers in the respiratory and reproductive systems for both primary cancer and SPC, whereas males showed a pronounced predominance in the digestive system. The top five primary cancer types were lung cancer (298 cases), breast cancer (117 cases), colorectal cancer (85 cases), thyroid cancer (60 cases), and esophageal cancer (54 cases). The top five SPCs were lung cancer (369 cases), colorectal cancer (108 cases), breast cancer (75 cases), thyroid cancer (61 cases), and gastric cancer (44 cases). Association analysis showed that 481 patients (52.4%) developed their SPC in the same organ system as their primary cancer, slightly more than the 437 patients (47.6%) with SPCs in different systems. Common cancer combination patterns included respiratory→respiratory (222 cases), digestive→digestive (147 cases), and reproductive→reproductive (60 cases). Among patients with second primary lung cancer, the proportion of adenocarcinoma was higher in females (170 cases) than in males (101 cases), while the proportion of squamous cell carcinoma was higher in males (53 cases) than in females (12 cases), indicating a statistically significant sex-related difference in pathological type distribution (P < 0.05).ConclusionThis large-sample study systematically reveals sex-based differences in the characteristics and associative patterns of SPCs. This study systematically defines sex-specific, high-risk cancer-system profiles (e.g., digestive-to-digestive in males, respiratory-to-respiratory and reproductive-to-reproductive in females) and establishes ‘anatomic system concordance’ as a fundamental principle in the development of SPCs. These findings provide a robust foundation for sex-specific and primary cancer type-guided surveillance strategies. Future clinical practice can utilize these findings to develop stratified management plans based on patient sex and initial primary cancer type, aiming to reduce the incidence and mortality of multiple primary malignant neoplasms.